Complex laboratory tests for determination of strength-deformability parameters in unsaturated conditions for sand from tailing dam - Papić, Jovan; Abazi, Sead; Peševski, Igor (My University, 2017)
One significant portion of the Earth’s surface is subjected to dry and semi-dry climatic conditions, and consequently, many of the soils in engineering practice are unsaturated. A specific type of structures where the change in the degree of saturation is a result of both climatic changes, as well as draining conditions are tailing dams. Tailing dams are objects of capital importance where the downstream slope is made of fine sand in wet condition. The draining reduces the saturation degree, which favorably influences the behavior of the dam. However, this aspect is not considered during their design, so there always remains the dilemma of "reserves" of shearing strength. Hence, the interest arises to study the properties of tailing sand in different conditions of saturation and to implement them in the numerical analysis for the calculation of stresses, strains and stability. Such dedicated tests are carried out at several high-educational institutions, and thereafter applied in the stability analyses. The obtained lab-numeric results contribute to the clarification of the role and influence of partial saturation on the shear strength, slope stability and deformability of tailing sand.
Keywords: tailing sand, degree of saturation, shearing resistance, deformability